Pitch Lake, Trinidad, B.W.I. - (:unkn) unknown (My University, 2009)
Photo of Pitch Lake in Trinidad. Some persons visible are observing while others are digging pitch.
Colour: Red, pink and White; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Pitch; Asphalt industry--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--La Brea; Ponds--Trinidad and Tobago; Forests and forestry--Trinidad and Tobago; [1910]; Men--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Hats--Trinidad and Tobago; Employees--Trinidad and Tobago; Work; Working class--Trinidad and Tobago; Blue collar workers--Trinidad and Tobago; Transportation--Trinidad and Tobago; Buildings--Trinidad and Tobago; Carriages and carts--Trinidad and Tobago; Draft animals--Trinidad and Tobago; Pitch Lake, The (La Brea)